2021
DOI: 10.3390/ijms221910530
|View full text |Cite
|
Sign up to set email alerts
|

N6-Isopentenyladenosine Hinders the Vasculogenic Mimicry in Human Glioblastoma Cells through Src-120 Catenin Pathway Modulation and RhoA Activity Inhibition

Abstract: Background: Vasculogenic mimicry (VM) is a functional microcirculation pattern formed by aggressive tumor cells. Thus far, no effective drugs have been developed to target VM. Glioblastoma (GBM) is the most malignant form of brain cancer and is a highly vascularized tumor. Vasculogenic mimicry represents a means whereby GBM can escape anti-angiogenic therapies. Methods: Here, using an in vitro tube formation assay on Matrigel, we evaluated the ability of N6-isopentenyladenosine (iPA) to interfere with vasculog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…This kinase is responsible of Y845 phosphorylation, which is important for the EGFR/EGFRvIII translocation to mitochondria, contributing to their integrity as much as to the survival of cancer cells [ 34 ]. Since, in our recent study, we demonstrated that iPA 10 μM at 24 h inhibited the Src Kinase phosphorylation in several GBM cells, including U87MG cells lines [ 22 ], we wondered whether iPA treatment might affect the phosphorylation status of Y845 of the EGFR/EGFRvIII and consequentially inhibit their translocation on mitochondria. We performed a 24 h time course of the phosphorylation status of Y845 in U87MG, U87MG-EGFRwt, and U87-EGFRvIII cells treated with iPA 10 μM in comparison with untreated cells and revealed the results through western blot analysis, using a specific antibody recognizing EGFR phosphorylated on tyrosine 845, pEGFRY845.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This kinase is responsible of Y845 phosphorylation, which is important for the EGFR/EGFRvIII translocation to mitochondria, contributing to their integrity as much as to the survival of cancer cells [ 34 ]. Since, in our recent study, we demonstrated that iPA 10 μM at 24 h inhibited the Src Kinase phosphorylation in several GBM cells, including U87MG cells lines [ 22 ], we wondered whether iPA treatment might affect the phosphorylation status of Y845 of the EGFR/EGFRvIII and consequentially inhibit their translocation on mitochondria. We performed a 24 h time course of the phosphorylation status of Y845 in U87MG, U87MG-EGFRwt, and U87-EGFRvIII cells treated with iPA 10 μM in comparison with untreated cells and revealed the results through western blot analysis, using a specific antibody recognizing EGFR phosphorylated on tyrosine 845, pEGFRY845.…”
Section: Resultsmentioning
confidence: 99%
“…Sanger sequencing method was used for analysis of codon 100 and 132 of IDH1 and codon 140 and 172 of IDH2 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, N6-isopentenyladenosine (iPA), an adenosine modified with an isopentenyl chain, a product of the mevalonate pathway, has been identified as a compound able to interfere with VM. IPA impaired this process by affecting the cytoskeletal structure of GBM cells reducing the formation of VM structures on matrix in vitro by the modulation of the Src/p120-catenin pathway and the inhibition of RhoA-GTPase activity [ 98 ].…”
Section: Gbm-associated Mechanisms Of Neovascularizationmentioning
confidence: 99%
“…Being a capacity of the tumour to provide by itself sufficient blood supply for its sustainment [20], VM refers to the ability of aggressive cancer cells to produce fluid-conducting vessel-like structures in an EC-independent way [21]. First discovered in uveal melanoma in 1999 [20], during the following 20 years, VM has been reported in several malignant tumours, including melanoma [22,23], glioblastoma [24,25], osteosarcoma [26,27], hepatocellular carcinoma [28,29], and breast [30,31], lung [32,33], gastric [19,34], colorectal [35,36] and prostate [37,38] cancers. VM is associated with a high tumour grade, invasion, metastasis and poor prognosis in patients with malignant tumours [39][40][41][42][43], including breast [44], colorectal [36], prostate [45], hepatocellular [46], lung [45], ovarian [47], gastric [48] and bladder [49] cancers.…”
Section: Introductionmentioning
confidence: 99%